(untitled) (Journal of Student Affairs in Africa, 2024)
The devastation and aftermath of the COVID-19 pandemic continue to pervade almost every sphere of human existence, albeit arguably increasingly nuanced. As we move into the post-pandemic world, it is essential to reflect on the lessons learned and forge transformed decolonialised ways of knowledge production in higher education. To ensure the continuation of academic socialisation, academic conference organisers have had to introduce virtual conferencing during the pandemic. In this paper, we discuss the experiences of students that attended the first online Southern African Students Psychology Conference (SASPC) during the pandemic in South Africa within an Open Distance e-Learning context. We use academic socialisation as a theoretical framework to understand student experiences attending the first online SASPC and to discuss the student conference as a site for decolonialisation. From the focus group discussion with student attendees, the historical and current format of the conference unexpectedly emerged as a colonised space of academic socialisation that the students challenged. Opportunities for using the student conference space as a site of decolonisation are explored to contribute to the dearth of scholarly literature aimed at actively incorporating student’s voices in the decolonialisation of academic spaces in the Global South.